2020
DOI: 10.1109/tvcg.2020.2986996
|View full text |Cite
|
Sign up to set email alerts
|

t-viSNE: Interactive Assessment and Interpretation of t-SNE Projections

Abstract: t-Distributed Stochastic Neighbor Embedding (t-SNE) for the visualization of multidimensional data has proven to be a popular approach, with successful applications in a wide range of domains. Despite their usefulness, t-SNE projections can be hard to interpret or even misleading, which hurts the trustworthiness of the results. Understanding the details of t-SNE itself and the reasons behind specific patterns in its output may be a daunting task, especially for non-experts in dimensionality reduction. In this … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(76 citation statements)
references
References 59 publications
1
75
0
Order By: Relevance
“…However, a previous anatomical study by Williams et al (38) has shown limited variance in ligament insertions between subjects. Finally, t-SNE clusters represent non-linear reductions in dimensionality, which remain difficult to interpret (39). Nevertheless, rapid evolving technology in this field has high potential for future algorithms interpreting these lowdimensional data clusters.…”
Section: Discussionmentioning
confidence: 99%
“…However, a previous anatomical study by Williams et al (38) has shown limited variance in ligament insertions between subjects. Finally, t-SNE clusters represent non-linear reductions in dimensionality, which remain difficult to interpret (39). Nevertheless, rapid evolving technology in this field has high potential for future algorithms interpreting these lowdimensional data clusters.…”
Section: Discussionmentioning
confidence: 99%
“…Before the advent of word embedding technology, one-hot representation is a traditional method, but one-hot is too sparse to reflect the interrelationship between words. In addition, the principal component analysis (PCA) 49 and the T-distributed neighborhood embedding algorithm (T-SNE) 50 can be adopted to further reduce the dimension of the distributed representation in the word embedding space, thereby realizing the visualization of word embedding and word meaning induction. In view of this, word embedding technology is utilized in this paper to realize the distribution representation.…”
Section: Openmentioning
confidence: 99%
“…As a solution, t-SNE method will replace the normal distribution used in the low-dimensional space with a t-distribution with 1 of freedom. The probability density function (PDF) of t-distribution is shown in (17) where v is expressed as a degree of freedom. When v=1, it can be simplified to formula (18).…”
Section: 1) Crowding Problemmentioning
confidence: 99%
“…Feature extraction also plays a vital role in data-driven fault diagnosis and dimensionality reduction for the samples or datasets [16]. Nevertheless, the principal component analysis (PCA) is commonly used to find the main components of the original data and establishes a direct relationship between the high and low dimensional data sets, but it cannot capture the non-linear pattern [17]. Therefore, this research uses the t-distribution stochastic neighbor embedding (t-SNE) to reduce the dimensionality of nonlinear data, which can visualize high-dimensional complex signal patterns.…”
Section: Introductionmentioning
confidence: 99%